Efficacy of Single Shot GnRH versus CIDR-PGF2α-GnRH-FTAI Protocol for the Treatment of Postpartum True Anestrus in Dairy Cattle - Mahat, Jayanta; Gautam, Gokarna; Pokharel, Aashirbad; Shah, Shatrughan (Journal of Agriculture and Forestry University, 2026)
Postpartum true anestrus is a major cause of reduced fertility and production, particularly in high-yielding crossbred dairy cows. Hormonal interventions under proper nutrition and management can restore reproductive function. This study compared two hormonal protocols for treating postpartum true anestrus in dairy cows. Forty-five postpartum anestrous cows were examined by transrectal palpation and ultrasonography to classify them as true anestrus or silent estrus. Among these, 73.3% had true anestrus and were included in the treatment trial (n=33). In treatment 1 (GnRH, n=13), cows received a single intramuscular injection of buserelin acetate (20 μg). In treatment 2 (CIDR-PGF2α-GnRH-FTAI, n=20), a CIDR device containing 1.9 g progesterone was inserted on day 0 and removed on day 7, with PGF2α (cloprosterol 500 μg) injected at removal. GnRH (20 μg) was administered on day 9, followed by fixed-time artificial insemination on day 10. Estrus induction rate did not differ significantly between GnRH (53.9%) and CIDR-PGF2α-GnRH-FTAI (60%) groups. The interval from treatment to estrus was shorter in the CIDR-based group (61.0±10.2 h) than in the GnRH group (163.7±36.0 h). Pregnancy rate tended to be higher in CIDR-PGF2α-GnRH-FTAI (55.0%) than in GnRH (23.1%, P=0.07). Cows with good body condition score (BCS) had higher pregnancy rate than those with poor BCS (P=0.05). Other factors, including milk yield, endoparasitic infection and anemia, had no significant effect. Single-shot GnRH was as effective as CIDR-PGF2α-GnRH-FTAI for estrus induction, while the CIDR-based protocol shortened the interval to estrus and tends to improve pregnancy outcomes.